Integrasi Lean Manufacturing dan Six Sigma Sebagai Upaya Minimasi Pemborosan dan Perbaikan Kualitas - Suparto, Suparto; Prastian, Lutfi Dwy (Institut Teknologi Adhi Tama Surabaya, 2025)
This research aims to minimizing waste and improve product quality is the key of success in business. PT. Romi Violeta is a company industri Manufacturing that engaged furniture based Making To Order. The problem that become a foundation research conducted these are it is known that the percentage of defect product in PT. Romi Violeta the most dominant is product wardrobes with the value of precentage as 13%. The purpose of this research to minimize waste and improve quality process production wardrobes in PT. Romi Violeta by giving improvement recommendations. Through the application of approach Lean Manufacturing, Six Sigma, Failure Mode and Effects Analtysis, as well as Fault Tree Analysis, waste can minimized and quality improvement. Results of this study reveals at PT. Romi Violeta found two waste the most effect namely waste defective product that get score of 3 and waste of delay that get score of 2,3. Solution fixes to minimize waste and quality improvement, by giving managerial implications against damage on the engine rip saw, and operator less scrupulous improvements that carried out effects occurrence non value added wardrobes of 6,25% become 3,59%.